2017
DOI: 10.1021/acs.jnatprod.7b00041
|View full text |Cite
|
Sign up to set email alerts
|

Structure Determination and Mechanism of Formation of a seco-Moreliane Derivative Supported by Computational Analysis

Abstract: Basic hydrolysis of a dichloromethane extract of Stevia lucida yielded (4R,5S,7R,9R,10R,11R)-7,9-dihydroxylongipin-2-en-1-one (1), which was oxidized and subjected to acidic conditions to generate the new seco-moreliane derivative 3. The structure of 3 was established based on NMR data interpretation and confirmed computationally. A plausible mechanism for the carbocationic rearrangement of the trione 2 to the seco-moreliane 3 was supported by DFT computations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…An interesting molecular rearrangement has been reported by Morales and co-workers [5]. They observed that triketone 5 on treatment with p-TSA in benzene resulted in the formation of a keto lactone 6, a 1-11 seco-moreliane derivative and also the first representative of this group (Figure 1).…”
Section: Acid Catalyzed Rearrangement Of Moreliane Based Triketone Csupporting
confidence: 53%
“…An interesting molecular rearrangement has been reported by Morales and co-workers [5]. They observed that triketone 5 on treatment with p-TSA in benzene resulted in the formation of a keto lactone 6, a 1-11 seco-moreliane derivative and also the first representative of this group (Figure 1).…”
Section: Acid Catalyzed Rearrangement Of Moreliane Based Triketone Csupporting
confidence: 53%